Sacralise space, delegitimize judges of faith. Graffiti, writings and drawings of the prisoners of the Holy Office (Palermo, 17th century) - Fiume, Giovanna (Huarte de San Juan. Geografía e Historia, 2024)
Within the monumental complex of Palazzo Chiaromonte, known as the Steri, currently the seat of University of Palermo, stands the building of the Secret Prisons, built in 1603 for the confinement of prisoners of the tribunal of the Spanish Holy Office while their trials were ongoing. On the walls, detainees left not only graffiti, writings, and drawings, but also names and dates that have allowed the tracing of the judicial documents concerning them (preserved in the Inquisición Sicilia collection of the National Historical Archive of Madrid and in the State Archive of Palermo); the information from the archival documentation and the drawings on the prison walls reveals the identities of the authors: their social status, age, charges, judicial behaviour, relationship with fellow prisoners, and the prison life of numerous groups of inmates, incarcerated for reasons of faith. Their biographical profiles shed light, on one hand, on the motivations behind this ‘writing art’, and on the other hand, on the iconographic models that inspire many graffiti and drawings.This reflects an effort to sanctify the prison, with the intention of taming a perilous and unfriendly environment that reflects the devotions, cults, and religious beliefs of a notable portion of the incarcerated population of the Ancien Régime. within some of these religious practices. It also reveals in some of them implicit contestation and subtle challenges to and delegitimisation of the authority of the judges.
Keywords: secret prison; Spanish Holy Office; graffiti, drawings and writings; sacralisation of prison space